(untitled) (Journal of Preventive and Social Medicine, 2021)
Background: Tannery is one of the key export-oriented sectors in Bangladesh and plays an important role in the country’s economy. But the manufacturing process in the tannery industry is hazardous for both workers, and the environment. This study was carried out to assess the perception and understanding of the tannery workers about the hazards in their workplace and related health problems suffered by them. Methods: lt was a cross-sectional study carried out in 25 tannery industries. A total of 200 workers who had at least one-year working experience in the studied tannery industries were included as the respondent of the study. Interviewer semi-structured questionnaire and hazard assessment checklist was used for data collection Results: Of the total participants’ majority (74%) were male and the mean age was 31.1±11.57 years. Most of the workers did not get any training related to their job and safety measures. The common hazards mentioned by the respondents were unsafe handling of chemicals (45.5%), unsafe machinery (37.0%), tanning process (24.5%), handling of machines /mater ials (23.5%) and poor housekeeping (25.5%). Other hazards as perceived by the participants were inadequate lighting , dust, noise , improper ventilation system, he at, slippery floor and inappropriate use of PPE. A majority (68.0%) of the respondents mentioned that they suffered from illnesses which were related to their work. The illnesses were skin problems (49.0%), respiratory problems (36.5%), musc uloskeletal dis orders (32.5%), eye problems (18.5%) and gastrointestinal problems ( 17.5%). The participant workers also mentio ned the lack of first aid and treatment facilities, no canteen and child’s room and limited welfare facilities in their industry. Conclusion: The workplace hazards perceived by the tannery workers revealed the real situation of the work process and the work environment, and did not differ much with the findings of the walk-through survey. The tannery workers also reported being suffered from several general and work-related diseases. JOPSOM 2020; 39(1): 31-42